THE IMAGERY DEALING WITH INDIAN CULTURE OF FUNERAL IN PHILIP MORIN FRENEAUâ€™S â€œTHE INDIAN BURYING GROUNDâ€ - Tataq Candraputi (Humaniora Scientia, 2014)
The main goal of this research is to discuss the imagery dealing with Indian culture in Philip Morin Freneauâ€™s â€œThe Indian Burying Groundâ€. This research has two purposes: (1) to analyze the imagery that shows the Indian culture of funeral, (2) to analyze the imagery that shows the Indian culture dealing with the life after the death. The theories which are used in this research are the theories of meaning, imagery, and setting. Moreover, structural and historical approaches are taken to analyze the data. Next, library research including internet browsing is used to support the data. Visual imagery, auditory imagery, and kinesthetic imagery are imageries that describe the Indian culture of funeral and describe the Indian culture dealing with the life after death. In the poem, the Indian culture of funeral is different from the other culture. The Indian have their own way to bury the dead. They have some procedures to bury the dead inherited by their ancestors from time to time. The Indian celebrate the funeral with many kinds of activities. They eat, play games, sing traditional songs to celebrate a joyous feast. The Indian belief of life after death is very strong. They believe the dead people continue their activities in spirit form. The dead Indian continue their activities, such as they sit together, share the joyous feast and hunt the animal in their life after the death. The Indian believe that the dead Indian stay in their own land, and they protect the land in spirit form. Keywords: imagery, culture, funeral, indians